PERILAKU PENJAMAH MAKANAN DALAM MENERAPKAN HIGIENE SANITASI MAKANAN DI PONDOK PESANTREN DARUL FALAH V KECAMATAN DIWEK KABUPATEN JOMBANG - Mohammad Nur Hamzah; Narwati .; Koerniasari . (Poltekkes Kemenkes Surabaya, 2015)
Pesantren is an Islamic boarding school for students to learn the various aspects of Islam. The educationsystem in pesantren Darul Falah V Diwek Jombang District requires students to stay in the dorms during theirentire learning period. Students are therefore required to stay and eat at the boarding school. This conditionrequires food handlers in boarding school to strictly apply food hygiene and sanitation principles in providingthe best possible food preparation services, so that nutritional needs are met and to prevent contaminationform of physical, chemical, and microorganisms that may threaten the health of the students.The results showed the characteristics of the food handlers, they are 100% female, 40% of them aged 20years, and 40% of them have service period of 1 years. In terms of their behavioral profile, 100% have agood knowledge, 100% indicating good attitude and 100% have good conduct. Overall evaluation of foodhygiene sanitation in Darul Falah V Islamic boarding school in Diwek Sub-District Jombang District resulted ina score of 82 %, thus its could not satisfy the designated standard, especially on the variables of buildingsand hygiene of food handlers.The conclusion of this study found that the behavior of food handlers have been good, but there was stillsome aspects of food hygiene practices need to be improved such as on personal hygiene. It is suggestedforfood handlers to provide monitoring and supervision of the sanitation of food processing plant by appointing asupervisor, produce posters containing warning and giving strict sanctions for handlers who do not carry outthe activities according to the existing rules.